Analysis of Regional Economic Problems (Case Study : Mapping Regency / City Leading Sectors in Papua Province in 2020) - Prabowo, Try Agung; Ananda, Candra Fajri; Bintoro, Nugroho Suryo (Journal of International Conference Proceedings, 2023)
Each region has its own model of economic growth, different from other regions, so planning the economic development of a region must take into account the economic, social and physical characteristics of the region itself, including its interaction with other regions. Based on data released by the Central Agency of Statistics, Papua is ranked as the province with the highest poverty rate in Indonesia at 26.80%, much higher than the national poverty rate. This study uses the Klassen Typology method and Location Quotient (LQ) analysis to group Papua Regencies/cities into several categories and to know the main sectors of Papua regencies/cities. so that economic development policies can be more targeted according to the potential of each region. In this study, it is known that most regencies/cities in Papua Province are categorized as (relatively) underdeveloped regions and it is also known that the most basic sectors in Papua are agriculture, forestry, and fisheries. Based on these results, it is expected that the Regency / city governments in Papua Province pay special attention, especially to areas in the category of underdeveloped sectors and further optimize the resources or potential sectors that exist in each region.